Pengaruh Sarana Prasarana dalam Menunjang Prestasi Belajar Siswa SD di Sekolah Indonesia Den Haag - Chusnul Inayah; Eva Luthfi Fakhru Ahsani; Emy Mastura; Laila Sittatun Ni’mah; Vina Amalia (Program Studi PGMI Sekolah Tinggi Ilmu Tarbiyah Nahdlatul Ulama Al Hikmah Mojokerto, 2021)
Infrastructure is a tool that supports the learning process provided by the school. Without the learning infrastructure, it does not work optimally. The motive of this observe become to determine the impact of facilities and infrastructure on the learning achievement of Primary School students at the Indonesian School in The Hague (SIDH). This form of studies is a qualitative studies with a descriptive approach. Data collection techniques thru interviews, FGD (focus group discussions) and documentation. The outcomes of this observe suggest that there are many differences between SIDH Primary Schools and Indonesian schools in terms of facilities and infrastructure. The difference lies in its completeness. The infrastructure at SIDH Primary Schools is very limited, but has advantages in internet connection and digital learning resources. Facilities and infrastructure below the auspices of the Ministry of Education and Culture and the Ministry of Foreign Affairs. There are elements that have an effect on the gaining knowledge of success of SIDH Primary Schools, particularly inner elements and outside elements. SIDH Primary Schools facilities and infrastructure are not the main factors affecting learning achievement. The lack of facilities and infrastructure does not deny the low learning achievement. With a small number of students, it is easier for teachers to guide and supervise students. So that they can learn optimally.